Overview of family resilience index in South Tangerang City during COVID-19 pandemic - Muhammad Iqbal,; Syifa Rasyida Adriani, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aimed to identify and map the level of family resilience in South Tangerang City to prevent family resilience problems. The family resilience level was measured using the family resilience measurement tool from Iqbal & Roebiyanto (2019). This research used a quantitative research approach with a descriptive analysis method. There were a total of 461 respondents in this study. Based on the results of calculations, scoring, and statistical analysis of each component of family resilience (physical resilience, psychological resilience, economic resilience, social resilience, and spiritual resilience), the results showed that the average score of the Family Resilience Index for South Tangerang City was 86.84 (very high). The highest score for family resilience was in Pondok Aren District (89.83), and the lowest was in Serpong District (83.47). For the physical health dimension, the highest score was in Setu District (16.07). Other dimensions such as psychological resilience (18.59), economic resilience (18.23), social resilience (19.06), and spiritual resilience (17.90) had the highest scores in Pondok Aren District. It is recommended that programs aimed at family resilience, COVID-19 handling, assistance and psychoeducation, and cooperation with other stakeholders in the community are necessary to strengthen the resilience of the families in South Tangerang City.